Early-Onset Shapiro Syndrome Variant Treated with Pizotifen: A Case Report. (3rd April 2017) - Denegri, Laura; Prato, Giulia; Mancardi, Maria Margherita; Schiaffino, Cristina; Striano, Pasquale; Baglietto, Maria Giuseppina
ABSTRACT: Shapiro Syndrome is a rare entity defined by the triad of recurrent spontaneous hypothermia, hyperhidrosis, and agenesis of the corpus callosum. Fewer than 100 cases have been reported so far and there are only few cases without a complete agenesis of corpus callosum ("Shapiro Syndrome Variant"). In this article, we report the clinical, electroencephalographic, and neuroimaging data of a patient with early-onset Shapiro Syndrome Variant. The case study describes a 4-year-old patient with episodes characterized by generalized hyperhidrosis, hypotonia, impaired consciousness, and hypothermia with onset before the first year of age. We captured an event during which the EEG showed rhythmic low- to medium-voltage theta waves without clear epileptiform activity. Brain MRI was normal and Shapiro Syndrome Variant was hypothesized. We started treatment with pizotifen, and after 2 years, the patient showed a reduction in frequency and duration of episodes. Shapiro Syndrome, although rare, should be considered in the differential diagnosis in patients with neurovegetative symptoms which suggest epileptic attacks at first. Our case is of particular interest to specialists because Shapiro Syndrome Variant is a rare syndrome and our patient had a very early onset of symptoms.In addition, we report our experience with pizotifen therapy, which produced a good response.